Stochastic simulation of destruction processes in self-irradiated materials - Patsahan, T.; Taleb, A.; Stafiej, J.; Holovko, M.; Badiali, J.P. (Condensed Matter Physics, 2017)
Self-irradiation damages resulting from fission processes are common phenomena observed in nuclear fuel
containing (NFC) materials. Numerous α-decays lead to local structure transformations in NFC materials. The
damages appearing due to the impacts of heavy nuclear recoils in the subsurface layer can cause detachments
of material particles. Such a behaviour is similar to sputtering processes observed during a bombardment of the
material surface by a flux of energetic particles. However, in the NFC material, the impacts are initiated from the
bulk. In this work we propose a two-dimensional mesoscopic model to perform a stochastic simulation of the
destruction processes occurring in a subsurface region of NFC material. We describe the erosion of the material
surface, the evolution of its roughness and predict the detachment of the material particles. Size distributions
of the emitted particles are obtained in this study. The simulation results of the model are in a qualitative
agreement with the size histogram of particles produced from the material containing lava-like fuel formed
during the Chernobyl nuclear power plant disaster. Самоопромiнення, що виникає внаслiдок процесiв подiлу радiоактивних елементiв, є звичним явищем,
яке спостерiгається в радiоактивних паливовмiсних матерiалах (ПВМ). Численнi α-розпади призводять до
перетворення локальної структури ПВМ. Ушкодження, якi виникають за рахунок ударiв вiддачi осколкiв
подiлу важких ядер в приповерхневому шарi, можуть спричинювати вiдокремлення частинок матерiалу.
Така поведiнка є подiбною до процесу розпилення, яке спостерiгається пiд час бомбардування поверхнi
матерiалу потоком енергетичних частинок. Проте, в ПВМ удари iнiцiюються в об’ємi матерiалу. В цiй роботi ми пропонуємо двовимiрну мезоскопiчну модель, з метою здiйснення стохастичного комп’ютерного
моделювання процесiв руйнування, що виникають в приповерхневiй областi ПВМ. Ми описуємо ерозiю поверхнi матерiалу, змiну її шорсткостi з часом i передбачаємо вiдокремлення частинок матерiалу.
У цьому дослiдженнi отримано розподiли розмiрiв вiдокремлених частинок. Результати комп’ютерного
моделювання якiсно узгоджуються iз гiстограмами розмiрiв розпилених частинок спостережених в лавоподiбних паливовмiсних масах, якi сформувалися пiд час Чорнобильської катастрофи.